Oral ketotifen and topical antibiotic therapy in the management of pruritus in prurigo nodularis: A randomized, controlled, single-blind, parallel study - Ashimav Deb Sharma (Wolters Kluwer Medknow Publications, 2013)
Aims: To evaluate the role of oral ketotifen and topical antibiotic therapy in the management of pruritus in prurigo nodularis (PN) patients. Materials and Methods: Twenty-seven patients with PN and a history of atopy with raised IgE were included in this study in a dermatology clinic. All patients had positive growth of Staphylococcus aureus on the lesional skin swab. All patients received topical halobetasol and oral hydroxyzine for 4 weeks. In addition, all patients in the study group received oral ketotifen and topical antibiotic therapy for 4 weeks. Randomization was performed by using a table of random numbers, and the participants were randomly allocated to one of the two groups in the study. The study was a single-blind study, and the blinding was done by the investigator. Results: Of the 14 patients in the study group, 9 had complete relief from pruritus by the end of first week, which was maintained till the end of 4 weeks. In the control group, mild to moderate reduction in the intensity of pruritus in the PN lesions of all patients were noted by the end of the first week. No further improvement in the level of pruritus was noted in the participants during the trial period. The treatment was well tolerated by the patients, and the adverse reactions of drugs were minimal in both groups. Conclusions: This study showed that oral ketotifen and topical antibiotic therapy can be helpful in the management of pruritus in PN patients.